1998
DOI: 10.1016/s1359-6454(98)00185-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal drag of the antiphase domain boundary motion

Abstract: AbstractÐThe antiphase domain boundary is a region in materials where ordering of atoms changes from one structural variant to another. The in¯uence of the internal energy excess on the dynamics of such a boundary is considered in the framework of the Onsager theory of linear response. The internal energy transport entails a temperature hump in the transition region and causes a drag e ect. An evolution equation that takes into account the ®nite thermal conductivity is derived. An experimental setup to reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The leading order temperature equation is (29) Integrating and matching with the outer solution twice in succession gives that u(O)…”
mentioning
confidence: 99%
“…The leading order temperature equation is (29) Integrating and matching with the outer solution twice in succession gives that u(O)…”
mentioning
confidence: 99%
“…Krzanowski and Allen, 43 and Cahn and Novick-Cohen 39 considered solute-drag effects at a migrating HOI. Umantsev 13 considered the influence of the internal energy excess on the dynamics of HOI in the framework of the Onsager theory of linear response and showed that such excess causes drag effect on the motion of HOI. The drag alters the effective interfacial mobility as follows:…”
Section: Homophase Interfacesmentioning
confidence: 99%
“…A number of questions, however, remained unaddressed by the simplified Onsager-type formulation in Ref. 13. For instance, what is the temperature distribution around the interface?…”
Section: Homophase Interfacesmentioning
confidence: 99%
See 2 more Smart Citations